What a Year of WFH has done to our Relationships at Work - Baym, Nancy; Larson, Jonathan; Martin, Ronnie (Harvard Business Review, 2021)
More than a year into the Covid-19 pandemic and WFH, new research from Microsoft shows that employees and teams are becoming much more siloed. In particular, connections with people outside our immediate teams has shrunk dramatically, leading to fewer places to connect around innovative ideas and fewer opportunities to build social capital. Further, this trend is making employees feel lonely and isolated. To help address this issue, leaders should focus on being proactive about connecting employees across the organization, make space for connections outside official meetings, encourage and reward social support, and improve the structure of meetings.